Choreographic objects: abstractions, transductions, expressions - Oliveira, Carlos Manuel Carvalho Santos (2016)
The present text attests a speculative tentative to define choreographic objects. Not only is this to be done by looking into a series of study cases, but also by looking so with a major concern: if such are the objects of choreographic knowledge, how can they be created anew? On the one hand, since all the cases discussed express knowledge by digital means, this question of novelty is to be framed by the “encounter between dance and technology”. On the other hand, since novelty is a potential outcome of process, this question is to be framed by the ontogenetic concerns of process philosophy. The method of inquiry here essayed can therefore be said to be an encounter in itself. To bring the encounter between dance and technology into contact with the conceptual framework of process philosophy is to problematize their potential relation and, in this way, to create conditions for resolving such problems into the form of propositional cases of solution. According to this, the encounter between dance and technology is itself a field of problematic relations. In the cases discussed, it attests the resolution of problems between dancing bodies and digital machines with each novel expression of choreographic knowledge. When looked upon by the ontogenetic concerns of process philosophy, these choreographic expressions are but particular cases of solution with regard to problems between potentials. Potentiality is therefore understood to be not only a fundamental condition of novelty but also the general field of relatedness in regard to which determinate cases stand as particular solutions. As such, to resolve a problem is always to propose one of its many potential solutions. To resolve the general question of novelty in the encounter between dance and technology is to express its potentials in the form of propositions. This is neither induction nor deduction, but rather transduction. As a mode of thought, transduction will also be argued to be characteristic of choreographic transmission. If a choreographic object is to be created anew, it needs to be transduced from the milieu of potentials wherein the knowledge of dance has formed. Transduction operates the passage between states of knowledge by moving the milieu and affecting in this way what is known with what is not (i.e. undetermined potentials). In this sense, choreography cannot be but an encounter between dance and technology: it structures the knowledge (logos) of dancing (tekhné) in determinate and transmittable ways. Because of this, it will be here contended that choreographic objects are both diagrammatic and algorithmic. Even before being expressed, they are structured in abstraction, i.e. diagrammatically. And they can only be expressed in different milieus because their structure is resumable, i.e. algorithmic. For this reason, the digital milieu presents itself as a most adequate medium to express choreographic knowledge. Notwithstanding, here, the question of novelty remains: how should the potentials of digital choreography be thought? By following such problem, this study will propose that the algorithmic computation of choreographic ideas is necessarily pervaded by incomputabilities and that novelty can be prompted by saturating the relationship between structures and potentials or, in other words, between what is known and the unknowable.